PERSEPSI, PENGETAHUAN, DAN PERILAKU REMAJA DALAM PEMBELIAN COMPACT DISC BAJAKAN - Jayanti, Tri Sapti; Djamaludin, Moh. Djemdjem; Latifah, Melly (Jurnal Ilmu Keluarga dan Konsumen, 2011)
This study aimed to analyze the differences between the perceptions, knowledge, and behavior of teenagers in behavior of pirated Compact Disc (CD) purchasing based on sex; the relationship between the variables of research, and variables that influence the behavior of pirated CD purchasing. Teenagers who became samples were 96 teenagers that selected randomly. The data were analyzed descriptively and also using independent sample t-test, correlation test, and regression test. The results showed that there was no difference between family characteristics, perceptions, knowledge, and behavior of pirated CDs purchasing of between male and female teenagers (p>0,05). The results also showed that there was a difference between spending money and budget that allocated to buy pirated CD between male and female teenagers (p<0,05). Correlation analysis showed that perception correlated significantly with knowledge about pirated CD. Pirated CD purchasing behavior influenced by pocket money and family income per capita.